2011
DOI: 10.1016/j.ajpath.2010.12.044
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Promotes Melanoma Metastasis through Enhanced Lymphangiogenesis

Abstract: The relationships of pregnancy and melanoma have been debatable. Our aim was to assess the influence of gestation on the course of melanoma in a classic murine model of tumor progression and in women. B16 mouse melanoma cells were injected in nonpregnant or pregnant mice on day 5 of gestation. Animals were evaluated for tumor progression, metastases, and survival. Tumor sections were analyzed for lymphatic and blood vessel number and relative surface and expression of angiogenic growth factors. Finally, primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 36 publications
6
39
0
3
Order By: Relevance
“…Consistent with the finding that AM promotes tumor progression, several studies report increased lymphangiogenesis and metastasis in pregnant women with melanoma when compared with non-pregnant melanoma patients [94,95]. The direct cause of the increased lymphangiogenesis remains unknown.…”
Section: Adrenomedullin-induced Lymphangiogenesis In the Reproductivesupporting
confidence: 57%
“…Consistent with the finding that AM promotes tumor progression, several studies report increased lymphangiogenesis and metastasis in pregnant women with melanoma when compared with non-pregnant melanoma patients [94,95]. The direct cause of the increased lymphangiogenesis remains unknown.…”
Section: Adrenomedullin-induced Lymphangiogenesis In the Reproductivesupporting
confidence: 57%
“…It has also been demonstrated that pregnancy promotes melanoma tumor growth via an increase in angiogenic and lymphangiogenic factors during the second and third trimesters [25,26]. Since angiogenesis appears to be an important feature of KS [27], the rise of these factors, especially vascular endothelial growth factors, could also play a major role in the recurrence and worsening of KS lesions during the second half of pregnancy.…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…Investigators have consequently resorted to experimental systems. In a murine model in which B16 melanoma cells were injected into recipient pregnant and nonpregnant control mice, for example, the pregnant state promoted tumor growth, metastasis, and mortality and correlated with an increase in intratumoral angiogenesis during gestation [ 149 ]. With respect to the epidemiological evidence, defi nitive conclusions as to the prognostic effects of pregnancy, if any, have historically been hampered by the small size of the datasets available for analysis and insuffi cient multivariate control for the effects of the major prognostic factors, especially Breslow thickness.…”
Section: Pregnancy Statusmentioning
confidence: 99%